Modelling IR Spectra of Sulfonated Polyether Ether Ketone (SPEEK) Membranes for Fuel Cells - Vaivars, Guntars; Krūkle-Bērziņa, Kristīne; Markus, Madara (Scientific.Net, 2020)
SPEEK (sulfonated polyether ether ketone) membranes have been prepared and characterized. The SPEEK membrane geometry and theoretical vibration spectra calculated using density functional theory (DFT) as depending from membrane chain length and polymer cross-linking. Analyzed the limitations of the method by comparing theoretical and experimental IR spectra.
Authors acknowledge support from LSC project No 2014/666 ERDF and students ( ) support from project 2DP/2.1.1.1.0/14/APIA/VIAA/009.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Sulfonated Poly(Ether Ether Ketone); Proton Conducting Membranes; ATR-IR spectra; Theoretical IR spectra